Tibet in the Western Imagination - Neuhaus, T.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Neuhaus explores the roots of the long-standing European fascination with Tibet, from the Dalai Lama to the Abominable Snowman. Surveying a wide range of travel accounts, official documents, correspondence and fiction, he examines how different people thought about both Tibet and their home cultures.
Keywords: Asia—History.; History, Modern; Asian History; Modern History